Towards a structural understanding of the fibrillization pathway in Machado-Joseph’s disease: trapping early oligomers of non-expanded ataxin-3 - Gales, Luís (2005)
Machado-Joseph’s disease is caused by a CAG trinucleotide repeat expansion that is translated into an abnormally long polyglutamine tract in the protein ataxin-3. Except for the polyglutamine region, proteins associated with polyglutamine diseases are unrelated, and for all of these diseases aggregates containing these proteins are the major components of the nuclear proteinaceous deposits found in the brain. Aggregates of the expanded proteins display amyloid-like morphological and biophysical properties. Human ataxin-3 containing a non-pathological number of glutamine residues (14Q), as well as its Caenorhabditis elegans (1Q) orthologue, showed a high tendency towards self-interaction and aggregation, under nearphysiological conditions. In order to understand the discrete steps in the assembly process leading to ataxin-3 oligomerization, we have separated chromatographically high molecular mass oligomers as well as medium mass multimers of non-expanded ataxin-3. We show that: (a) oligomerization occurs independently of the poly(Q)-repeat and it is accompanied by an increase in b-structure; and (b) the first intermediate in the oligomerization pathway is a Josephin domain-mediated dimer of ataxin- 3. Furthermore, non-expanded ataxin-3 oligomers are recognized by a specific antibody that targets a conformational epitope present in soluble cytotoxic species found in the fibrillization pathway of expanded polyglutamine proteins and other amyloid-forming proteins. Imaging of the oligomeric forms of the non-pathological protein using electron microscopy reveals globular particles, as well as short chains of such particles that likely mimic the initial stages in the fibrillogenesis pathway occurring in the polyglutamine-expanded protein. Thus, they constitute potential targets for therapeutic approaches in Machado-Joseph’s disease, as well as valuable diagnostic markers in disease settings.